问题 解答题
先化简,再求值:(
x+3
x2-3x
-
x-1
x2-6x+9
)÷
9-x
x2-3x
,其中x=2.
答案

解法一:原式=[

x+3
x(x-3)
-
x-1
(x-3)2
9-x
x(x-3)
,(1分)

=[

(x+3)(x-3)
x(x-3)2
-
x(x-1)
x(x-3)2
9-x
x(x-3)
,(2分)

=

x2-9-x2+x
x(x-3)2
÷
9-x
x(x-3)

=

x-9
x(x-3)2
x(x-3)
9-x
,(3分)

=-

1
x-3
.(4分)

∴当x=2时,原式=-

1
2-3
=1.(5分)

解法二:(

x+3
x2-3x
-
x-1
x2-6x+9
)÷
9-x
x2-3x

=[

x+3
x(x-3)
-
x-1
(x-3)2
]•
x(x-3)
9-x
,(1分)

=

x+3
x(x-3)
x(x-3)
9-x
-
x-1
(x-3)2
x(x-3)
9-x
,(2分)

=

x+3
9-x
-
x(x-1)
(x-3)(9-x)
,(3分)

=-

1
x-3
.(4分)

∴当x=2时,原式=-

1
2-3
=1.(5分)

单项选择题
填空题